The Prosperity Gospel in the African Diaspora: Unethical Theology or Gospel in Context? - Vähäkangas, Mika (Exchange, 2015)
The prosperity gospel in the Redeemed Christian Church of God, Hosanna Chapel, Helsinki, Finland, builds primarily on African indigenous worldviews rather than serving as a theological justification for capitalism. It is a contextual African interpretation of the gospel in a situation of tension between the expectations of extended families back home, those of the new society in which the immigrants find themselves, and the church. The African experience and heritage come to the fore especially in the strong emphasis placed on interpersonal relations, particularly with family members and God, as an essential part of prosperity. Naïve faith in the bliss of equal opportunities within capitalism is moderated by differentiation between realistic economic expectations and the special blessings that are endowed upon believers. When condemning the prosperity gospel wholesale, there is the risk of misinterpreting non-Western theologies and of morally castigating the weakest for their attempts to survive global capitalism instead of combating its oppressive structures.